ANALISIS DESKRIPTIF PERKEMBANGAN PERBANKAN SYARIAH DI ASIA TENGGARA - Ali Rama (Tauhidinomics: Journal of Islamic Banking and Economics, 2015)
Current statistic shows that Southeast Asia region has transformed as leading center for global Islamic financial industry. Indonesia and Malaysia are the leading countries for Islamic finance industry in the region. The study aims to provide a descriptive analysis of Islamic finance development in Souheast Asia countries, namely Indonesia, Malaysia, Brunei Darussala, Singapore, Thailand, and Philipine. The study focuses on the history and regulatory analysis for Islamic finance industry across jurisdiction. It finds that the regulation governs for Islamic financial institutions in each countries are varies. These differences will be a challenge in creation of Islamic finance integration as a part of ASEAN economic integration programm.